Acute Toxicity Evaluation of A Combined Extract (Mitragyna Speciosa and Lagerstroemia Speciosa) Leaves in Rats: Hematological, Biochemical and Histopathological Examinations - Pusarattanawong, Janejira; Ruanglertboon, Warit; Boonsri, Boonyakorn; Limsuwanchote, Supattra; Wungsintaweekul, Juraithip; Thipart, Kornsuda (Trends in Sciences, 2025)
Mitragyna speciosa and Lagerstroemia speciosa are traditional herbal medicines and are claimed to possess hypoglycemic effects. The current study aimed to evaluate the acute toxicity of a 1:1 ratio combined extract (CE) of these herbal medicines, using an animal model, to provide a safety assessment for concomitant use. Methanolic extractions were performed on the dried powder of each herb, followed by quantification of the active compounds (mitragynine and corosolic acid) using high-performance liquid chromatography (HPLC) techniques. For the acute toxicity study, a total of 12 adult female Sprague-Dawley rats (5 weeks old, weighing 200 - 250 g) were randomly assigned to control and CE groups, with 6 rats in each group. A single oral dose of 2,000 mg/kg body weight of the CE was orally administered to the animals, with monitoring conducted in accordance with OECD Guideline 420. Behavioral, hematological and biochemical profiles were collected at the end of the 14-day study period, followed by a post-mortem histopathological examination to assess tissue integrity in vital organs. Statistical analyses were conducted to identify significant differences in all available parameters. The results demonstrated no signs of aberrant toxicity in any of the collected parameters, which was further confirmed by histopathological examination, focusing on the liver and kidneys. The study concluded that the CE at a 1:1 ratio exhibited a favorable safety profile and could be classified as having low toxicity based on the Globally Harmonized System. However, long-term studies are recommended to further confirm their safety profile. HIGHLIGHTS Oral gavage of the combined extract of Mitragyna speciosa and Lagerstroemia speciosa (1:1) demonstrated no toxicity or mortality in a single-dose acute toxicity test. No abnormalities were observed in animals’ behavior, food intake, or water consumption compared to the control group. Similarly, biochemical and hematological parameters showed no significant differences between groups, remaining within the normal reference range. Histopathological analysis of the liver and kidneys revealed no signs of deformities in the combined extract group, providing strong evidence of no anatomical alterations. GRAPHICAL ABSTRACT